Can Health Perceptions, Credibility, and Physical Appearance of Low-Fat Foods Stimulate Buying Intentions? - Inés Küster-Boluda; Natalia Vila (Foods, 2020)
This study examines the influence of labelling and packaging strategies on perceived product health and overall attitudes to low-fat products in the field of healthy food claims among young consumers. The aim was to determine if these aspects can influence buying intentions. After a literature review, a quantitative study was carried out. With a sample of 300 young consumers (18–25 years old) and the use of partial least square methodology, this paper demonstrated that: (1) nutritional information and visual cues affect consumers’ perceptions (information credibility and physical appearance), (2) information credibility influences product health perceptions and attitudes toward a product, (3) physical appearance affects attitudes toward a product, and (4) overall attitude to the product influences purchase intentions The results achieved show that credibility and physical appearance could stimulate low-fat foods purchase intentions through a positive global attitude to the product. Additionally, nutritional information and visual cues play a more relevant role than nutritional information response and informative cues. These results and the conclusions that follow must be understood in the analysed context (low-fat foods) with the sample used (300 young consumers).